Wavelength monitoring with low-contrast multimode interference waveguide - Sookdhis, Chrisada (2010)
We demonstrate a wavelength monitor based on interference effect in planar quantum-well waveguide fabricated using argon plasma quantum-well intermixing. The passive device exhibits a characteristic curve, which is used to determine the wavelength of an arbitrary input light near the 1550-nm window. It has an exponential-like wavelength response in the wavelength range 1520-1620 nm and resolution of 0.2 nm.